Crisis management during anaesthesia: sepsis. Issue 3 (2nd June 2005) - Myburgh, J A; Chapman, M J; Szekely, S M; Osborne, G A
Abstract : Background: Anaesthesia with concurrent sepsis is risky, and involves consideration of possible organ dysfunctions—respiratory, cardiovascular, renal, and haematological—as well as ensuring that appropriate antibiotics are given after taking the necessary microbiological specimens. Because prompt attention needs to be paid to so many body systems, the place for a structured approach during anaesthesia for a septic patient was assessed. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for sepsis, in the management of sepsis occurring in association with anaesthesia. Methods: The potential performance of this structured approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: Sepsis was identified as the primary problem in 13 of the first 4000 reports (<1%) to AIMS. The incidents reported generally occurred in sick patients; 70% were ASA status III or worse. The COVER ABCD algorithm provided a diagnosis and corrective manoeuvre in only 15% (2/13) of reported incidents, and the sepsis sub-algorithm provided adequate therapeutic strategies in a further 38% (5/13) of the incidents. Eight cases required the use of additional sub-algorithms for desaturation (30%), cardiac arrest (15%), hypotension (8%), and aspiration (8%). Conclusion: Sepsis involves a serious physiological stress upon multiple organ systems. The use of a structured approach involving a core algorithm and additional sub-algorithms as required provides a series of checklists that can successfully deal with the complex multiple and interrelating problems that these patients present.